Penguatan Kelembagaan Bumdes untuk Pembangunan Desa di Kecamatan Rancakalong - Kurniawan, Iwan; Asri, Melati Dewi; Fitriani, Laksmi; Priatna, Ramdani (Politeknik STIA LAN Bandung, 2023)
The formation of BUMDes is a step to empower the economy and welfare of village communities. This must be supported by good management so that the potential in the village which has economic value can be developed massively in order to improve the welfare of the village community. However, managing BUMDes is not easy in the implementation process and requires strengthening from the institutional side. This community service (PkM) activity aims to help better manage BUMDes for village development. The implementation of this PkM took the form of a workshop and visits to several BUMDes in Rancakalong Subdistrict. Rancakalong Subdistrict has 10 villages and each village has a BUMDes. The results of PkM activities can be obtained that BUMDes managers know that BUMDes management is not based on the wishes of village leaders but on village deliberations to provide welfare for the community, especially the village economy, exploring village potential must be based on data collected in a system, and increasing capacity for BUMDes managers. a more professional one. Therefore, strengthening BUMDes must be carried out periodically and in a structured manner for the progress of BUMDes itself.